If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -5)(x + 6) = 0 Reorder the terms: x(-5 + 2x)(x + 6) = 0 Reorder the terms: x(-5 + 2x)(6 + x) = 0 Multiply (-5 + 2x) * (6 + x) x(-5(6 + x) + 2x * (6 + x)) = 0 x((6 * -5 + x * -5) + 2x * (6 + x)) = 0 x((-30 + -5x) + 2x * (6 + x)) = 0 x(-30 + -5x + (6 * 2x + x * 2x)) = 0 x(-30 + -5x + (12x + 2x2)) = 0 Combine like terms: -5x + 12x = 7x x(-30 + 7x + 2x2) = 0 (-30 * x + 7x * x + 2x2 * x) = 0 (-30x + 7x2 + 2x3) = 0 Solving -30x + 7x2 + 2x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-30 + 7x + 2x2) = 0 Factor a trinomial. x((-6 + -1x)(5 + -2x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 3
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Solution
x = {0, -6, 2.5}
| 2/3x=-7 | | 5/6/8 | | n/9-4=11 | | 125x+3=52x+4 | | 0.4p-2=0.8p-3 | | 8x+2(x-9)=82 | | -7x=-4 | | 93x=27 | | 0=5.1x+0.3x | | 8x+12(x-9)=82 | | 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 |